2019
DOI: 10.1111/cgf.13812
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Geometric Approach for Palette‐based Image Decomposition and Recoloring

Abstract: Palette‐based image decomposition has attracted increasing attention in recent years. A specific class of approaches have been proposed basing on the RGB‐space geometry, which manage to construct convex hulls whose vertices act as palette colors. However, such palettes do not guarantee to have the representative colors which actually appear in the image, thus making it less intuitive and less predictable when editing palette colors to perform recoloring. Hence, we proposed an improved geometric approach to add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…Region colors are represented as linear blends between (at most two) colors in a compact, representative palette. Recoloring is easily accomplished by adjusting the palette colors themselves and updating the apparent region colors by remixing with the same blending weights, as in palette‐based image recoloring approaches [CFL*15b, TLG16, WLX19].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Region colors are represented as linear blends between (at most two) colors in a compact, representative palette. Recoloring is easily accomplished by adjusting the palette colors themselves and updating the apparent region colors by remixing with the same blending weights, as in palette‐based image recoloring approaches [CFL*15b, TLG16, WLX19].…”
Section: Methodsmentioning
confidence: 99%
“…They proposed to simplify the convex hull until a user‐selected palette size p is reached. Wang et al [WLX19] observed that convex‐hull‐based palettes are sensitive to outliers. To reduce outlier sensitivity, they formulated an optimization problem to refine the simplified convex hull palette to make it more compact.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations